After ever after - Sonnenblick, Jordan (New York : Scholastic Press, 2010)
Although Jeff and Tad, encouraged by a new friend, Lindsey, make a deal to help one another overcome aftereffects of their cancer treatments in preparation for eighth-grade graduation, Jeff still craves advice from his older brother Stephen, who is studying drums in Africa.
A Junior Library Guild selection
Keywords: Cancer -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Family life -- New Jersey -- Fiction; Brothers -- Fiction; New Jersey -- Fiction; Cancer -- Patients -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Families -- New Jersey -- Juvenile fiction; Brothers -- Juvenile fiction; New Jersey -- Juvenile fiction